Integrating food biodiversity into public food procurement: a Brazilian Amazon case of Indigenous Peoples and local communities - Cabral da Conceição, Bianca; Borelli, Teresa; das Graças Ferreira Frazao, Andrea; Tomchinsky, Bernardo; Mendonce, Sharon; Hunter, Danny (2025)
This study explores the integration of food biodiversity and Indigenous Peoples (IPs) and Local Communities (LCs) into public food procurement. Using a primarily qualitative approach, it combines a scoping review with a case study of Brazil's National School Feeding Program (PNAE) and the Food Acquisition Program (PAA) across six municipalities in the eastern Amazon of Brazil. Common barriers included rigid procurement guidelines, culturally inappropriate menus, and erosion of traditional knowledge, reflecting the marginalization of Indigenous Peoples, as well as food biodiversity. Compared to the PNAE, the PAA exhibited stronger inclusion of IPs and LCs by integrating diverse foods, implementing “Indigenous” and “traditional” procurement modalities, and fostering social engagement. In the PNAE, culturally adapted menus for IPs and LCs were absent; however, the presence of unprocessed menu items positively correlated with food biodiversity. Strategies such as institutionalizing hybrid governance, participatory mechanisms, and social participation can strengthen IPs and LCs and biodiversity, thus providing pathways for PFP to support equitable, resilient, and culturally grounded food systems while addressing global challenges.